The Role of the Prophet in Peacebuilding in Medina - zul, Zulkarnain Harahap; Sri Wahyuni; Ridho Putra Saleh; Fathimah Azzahrah (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
The background of this study lies in the importance of understanding the diplomatic strategies employed by the Prophet Muhammad in resolving conflicts among the Arab tribes. The objective of this research is to examine the strategies used by the Prophet Muhammad in forming peace agreements, fostering harmonious relations among tribes, and consolidating the foundation of the Islamic state in Medina. This study adopts a qualitative research approach with a historical perspective. The data collection technique used is the analysis of Islamic historical sources such as the Quran, Hadith, and historical literature. The data obtained are analyzed using descriptive analysis techniques. Data validation is conducted through source triangulation to ensure the accuracy of information. The research findings indicate that the role of the Prophet Muhammad in promoting peace includes acting as a mediator in conflicts, as well as being a builder of justice and reconciliation in the diverse Medina community. In conclusion, a profound understanding of the Prophet Muhammad's role in peace in Medina provides valuable insights into the relevant principles of Islamic diplomacy to the present day.